2016
DOI: 10.54386/jam.v18i2.939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-seasonal temperature on wheat at different locations of India: A study using CERES-Wheat model

Abstract: CERES-Wheat model (DSSAT v 4.5.0.0) was used to analyze the effects of rise in intra-seasonal temperature on productivity of wheat and to optimize sowing time for mitigating the effects of rise in intraseasonal temperature at seven wheat growing locations representing different zones of India. The results showed that the temperature rise had differential effect on wheat yield in different zones and also with dates of sowing. Central zone(Udaipur and Raipur) was the most susceptible (yield reduced upto 10.2%) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, for average data, it was non-significant. The highest BY for -2016, and 2016was observed with HD-2733 Varieties had a non-significant effect on harvest index (HI) except for the years 2014-2015 (Table 7). The highest HI for 2014-2015 was recorded with HD-2824 (40.66), which was comparable with HD-2733 (40.35).…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for average data, it was non-significant. The highest BY for -2016, and 2016was observed with HD-2733 Varieties had a non-significant effect on harvest index (HI) except for the years 2014-2015 (Table 7). The highest HI for 2014-2015 was recorded with HD-2824 (40.66), which was comparable with HD-2733 (40.35).…”
Section: A B Cmentioning
confidence: 99%
“…Wheat production in Indo-Gangetic Plains is vulnerable to short-term temperature extremes (Lobell et al, 2012). Prevalence of dry westerly wind and sudden rise of temperature during the fag end of the growing season tends to shorten the grain filling period (Garg et al, 2013;Sandhu et al, 2016;Vashisth et al, 2020) and negatively impact grain setting of wheat (Sattar and Srivastava, 2021). It significantly affects growth and photosynthetic efficiency (Wang et al, 2011) and consequently reduces biomass and productivity (Farooq et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of wheat sowing is delayed in the region beyond the period of 25 November, forcing the crop to encounter higher temperatures (terminal heat) during the growing season (end of February to March) (Sattar et al, 2023). Therefore, terminal heat stress associated with dry westerly wind is a serious climatic constraint for successful wheat cultivation in India, particularly when it occurs during the grain-filling stage (Sandhu et al, 2016;Sattar et al, 2020). In one study on wheat, Poudel et al (2021) observed that the optimum temperature during the anthesis and grain-filling stage ranges from 12 to 22°C.…”
Section: Introductionmentioning
confidence: 99%
“…Models can be used to predict crop growth, development and yield as a function of soil, climate, weather, and crop management conditions. Crop simulation models have been used to study the effect of intra-seasonal variation in temperature on yield of wheat in India [8]. Patil et.…”
Section: Introductionmentioning
confidence: 99%